Overweight, obesity and risk of multimorbidity: A systematic review and meta‐analysis of longitudinal studies - Delpino, Felipe Mendes; Santos Rodrigues, Ana Paula; Petarli, Glenda Blaser; Machado, Karla Pereira; Flores, Thaynã Ramos; Batista, Sandro Rodrigues; Nunes, Bruno Pereira (Obesity reviews, 2023)
Summary This study aimed to review and quantify the association between overweight and obesity in the risk of multimorbidity among the general population. We conducted a systematic review and meta‐analysis in the databases of Pubmed, Lilacs, Web of Science, Scopus, and Embase. We included cohort studies that assessed the association between overweight and/or obesity with the risk of multimorbidity. The Newcastle‐Ottawa assessed the studies' individual quality. A random‐effect model meta‐analysis was performed to evaluate the association between overweight and obesity with the relative risk (RR) of multimorbidity; the I2 test evaluated heterogeneity. After excluding duplicates, we found 1.655 manuscripts, of which eight met the inclusion criteria. Of these, seven (87.5%) evidenced an increased risk of multimorbidity among subjects with overweight and/or obesity. Overall, we observed an increased risk of multimorbidity among subjects with overweight (RR: 1.26; CI95%: 1.12; 1.40, I2 = 98%) and obesity (RR: 1.99; CI95%: 1.45;2.72, I2 = 99%) compared to normal weight. According to the I2 test, the heterogeneities of the meta‐analyses were high. The Newcastle‐Ottawa scale showed that all studies were classified as high quality. Further longitudinal studies are needed, including different populations and stratifications by sex, age, and other variables.